Hashtag campaigns during the COVID-19 pandemic in Malaysia : escalating from online to offline - Leong, Pauline Pooi Yin; Amirul Adli Rosli (Trends in Southeast Asia, 2021)
Hashtag campaigns on social media enable users to express their sentiments on various issues and mobilize people to be part of a movement or cause; they have been used effectively by disenfranchised members of society against powerful elites.While some are of the opinion that online campaigns are ineffective due to ""slacktivism"", such campaigns can spill over to offline protests, especially if there are strong emotions such as anger, or a sense of injustice or social deprivation, spurring people on.The earlier hashtag campaigns in Malaysia--#AntaraDuaDarjat (#BetweenTwoStatus) and #DengkiKe.